Activated carbon-based desulfurizing agent and preparation method thereof

The activated carbon-based desulfurizer prepared through the steps of pickling treatment and multi-metal salt loading solves the problems of poor chlorine resistance, low sulfur capacity and high energy consumption in blast furnace gas, and achieves high efficiency and low energy consumption sulfide removal effect.

CN119909696AActive Publication Date: 2025-05-02YUEYANG XINGCHANG PETRO CHEM +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510396902.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

In the prior art, methods for reducing sulfur content in blast furnace gas have problems such as poor chlorine resistance, low sulfur capacity, poor removal effect on COS and high removal energy consumption.

Method used

The modified activated carbon is treated with pickling and a combination of cerium salt, iron salt and vanadium salt are loaded and chlorine-resistant hydrophobic treatment to form an efficient activated carbon-based desulfurization agent. The method includes the steps of pickling treatment, cerium salt loading, iron salt and vanadium salt combined loading, anti-chlorine hydrophobic treatment and calcination activation.

Benefits of technology

The sulfur capacity of activated carbon-based desulfurizer is improved to 44%~48%, the removal rate of COS and CS2 is enhanced, reaching more than 98%, the removal rate of H2S is increased more than 99%, and the tolerance to Cl- is significantly improved, reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909696A_ABST
    Figure CN119909696A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of blast furnace gas desulfurization, in particular to an activated carbon-based desulfurizer and a preparation method thereof. The desulfurizer is prepared by the method. The method comprises the steps of acid pickling treatment of waste activated carbon to obtain modified activated carbon, cerium salt loading, ferric salt and vanadium salt combined loading, chlorine-resistant hydrophobic treatment and roasting activation, and the desulfurizer is obtained. The sulfur capacity of the prepared activated carbon-based desulfurizing agent can be increased to 44%-48%, the activation energy on sulfides can be reduced, organic sulfur and inorganic sulfur can be catalyzed at the temperature of 20-50 DEG C, and energy consumption is greatly reduced; wherein the removal rates of carbonyl sulfide and carbon disulfide are both greater than or equal to 98%, and the removal rates of H2S are both greater than or equal to 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of blast furnace gas desulfurization, and in particular to an activated carbon-based desulfurizer and a preparation method thereof. Background Art

[0002] Blast furnace gas is a combustible gas produced as a byproduct of the steel smelting process, with a total sulfur content of 80~200mg / m 3 , of which organic sulfur (mainly carbonyl sulfide COS and carbon disulfide CS2) accounts for as high as 75%~85%, and inorganic sulfur (mainly H2S) accounts for 15%-25%. These sulfides are converted into SO2 after the combustion of blast furnace gas, which increases the burden on the flue gas desulfurization facilities of steel enterprises, makes it difficult to handle by-products, and makes it difficult to meet the ultra-low emission requirements of SO2 (the requirement is SO2 emission concentration ≤35mg / m³).

[0003] How to reduce the sulfur content in blast furnace gas is a hot topic in the industry. At present, the industry mostly uses hydrolysis process, adsorption process, activated carbon-based desulfurizer or wet oxidation method to reduce the sulfur content in blast furnace gas. Specifically, in the hydrolysis process, COS and CS2 are first hydrolyzed into H2S using a catalyst (such as Al2O3-based or Fe2O3-based catalyst), and then H2S is removed; however, the catalyst is reacted with Cl in blast furnace gas. - (Cl in blast furnace gas - The content is 10~500mg / m³) and Cl - Poisoning, showing poor chlorine resistance. In the adsorption process, porous materials (such as molecular sieves or modified activated carbon) are used to directly adsorb COS and CS2, but the sulfur capacity is low (such as 8wt%~12wt%), and the adsorption capacity for COS and CS2 is weak. In terms of activated carbon-based desulfurizers, there are generally problems such as complex preparation process, low sulfur capacity (such as the sulfur capacity of silicon-modified activated carbon is generally 8wt%~10wt%), and high temperature (such as 120°C) is required for desulfurization. In addition, silicon-modified activated carbon is not very resistant to Cl in blast furnace gas. - The tolerance is less than 200mg / m³, showing poor chlorine resistance. In the wet oxidation method, although H2S can be removed to less than 10mg / m³ and the sulfur recovery rate is >90%, the equipment occupies a large area and needs to be equipped with a sulfur recovery system, which increases the investment cost.

[0004] In addition, the chemical properties of COS in blast furnace gas are stable and require high temperature (above 200°C) or strong catalytic conditions to be converted, resulting in poor COS removal effect and high removal energy consumption.

[0005] In summary, it is necessary to provide an activated carbon-based desulfurizer and a preparation method thereof to solve the problems of poor chlorine resistance, low sulfur capacity, poor COS removal effect and high removal energy consumption existing in the prior art. Summary of the invention

[0006] The object of the present invention is to provide an activated carbon-based desulfurizer and a preparation method thereof. The specific technical scheme is as follows: In a first aspect, the present invention provides a method for preparing an activated carbon-based desulfurizer, comprising: Step S1, pickling treatment, mixing nitric acid and hydrogen peroxide in a mass ratio of 3-5:1 to form a mixed solution; mixing the waste activated carbon with the mixed solution in a mass ratio of 1:2-5, and then sequentially subjecting the mixture to ultrasonic treatment, rinsing treatment and first drying treatment to obtain modified activated carbon; Step S2, cerium salt loading, immersing the modified activated carbon in a cerium salt solution, and after a first immersion treatment and a second drying treatment, obtaining a cerium salt loaded modified activated carbon; Step S3, iron salt and vanadium salt combined loading, after the iron salt solution and the vanadium salt solution are mixed according to the molar ratio of iron to vanadium of 1:0.3-0.5, an organic acid is added, mixed, and a combined salt solution is obtained, and the pH value thereof is adjusted to 3-4; in the combined salt solution, the mass concentration of the organic acid is 1%-2%; The modified activated carbon loaded with the cerium salt is immersed in the combined salt solution, and after a second immersion treatment and a third drying treatment, a modified activated carbon loaded with a combination of iron salt and vanadium salt is obtained; Step S4, chlorine-resistant and hydrophobic treatment, immersing the modified activated carbon treated in step S3 in an alcohol solution containing a silane coupling agent, and sequentially undergoing a third immersion treatment and a fourth drying treatment to obtain chlorine-resistant and hydrophobic modified activated carbon; Step S5, calcination activation, the chlorine-resistant and hydrophobic modified activated carbon is first subjected to a first calcination treatment in an inert atmosphere, and then subjected to a second calcination treatment in an air atmosphere, and finally a calcined and activated activated carbon-based desulfurizer is obtained.

[0007] Optionally, in the pickling treatment, the mass concentration of the nitric acid is 3.5% to 4.5%; the mass concentration of the hydrogen peroxide is 0.8% to 1.2%; The ultrasonic treatment uses an ultrasonic frequency of 30-50kHz, an ultrasonic power of 300-600W, and an ultrasonic time of 1-2h; during the ultrasonic treatment, the temperature of the mixed solution is controlled to be 40-60°C; The rinsing treatment uses hot water to rinse the activated carbon after ultrasonic treatment until the pH value of the water flowing out after rinsing is 6-7; the temperature of the hot water is 60-80°C; The first drying process uses a drying temperature of 100-120° C. and a drying time of 3-5 hours.

[0008] Optionally, the cerium salt solution includes a Ce(NO3)3 solution; the mass concentration of the Ce(NO3)3 solution is 3.5% to 4.5%; The first soaking treatment adopts a soaking time of 3-5 hours and a soaking temperature of 20-30°C; The second drying process uses a drying temperature of 100-120° C. and a drying time of 2-4 hours.

[0009] Optionally, the iron salt solution includes a Fe(NO3)3 solution; the mass concentration of the Fe(NO3)3 solution is 18% to 22%; The vanadium salt solution includes NH4VO3 solution; the mass concentration of the NH4VO3 solution is 6% to 8%; The second soaking treatment adopts a soaking time of 10-14 hours and a soaking temperature of 20-30°C; The second immersion treatment is completed while the combined salt solution is stirred at a stirring speed of 50 rpm; The third drying process uses a drying temperature of 100-120° C. and a drying time of 15-20 hours.

[0010] Optionally, the waste activated carbon is waste activated carbon that adsorbs non-polar or weakly polar pollutants; the specific surface area of ​​the waste activated carbon is greater than or equal to 800 m 2 / g, ash content is less than or equal to 10%; The organic acid includes citric acid.

[0011] Optionally, dilute nitric acid is used to adjust the pH value of the combined salt solution to 3-4; the mass concentration of the dilute nitric acid is 5%-8%.

[0012] Optionally, the mass concentration of the silane coupling agent in the alcohol solution is 2% to 2.5%; the silane coupling agent includes KH-550; The third soaking treatment adopts a soaking time of 0.5-2 hours and a soaking temperature of 20-30°C; The fourth drying process adopts a drying temperature of 100-120° C. and a drying time of 3-5 hours.

[0013] Optionally, the heating rate used in the first roasting treatment is 2-5°C / min, until the temperature reaches a target roasting temperature of 200-300°C, and the holding time is controlled to be 1-3h.

[0014] Optionally, the heating rate used in the second roasting treatment is 2-5°C / min, until the temperature reaches a target roasting temperature of 300-500°C, and the holding time is controlled to be 2-4h.

[0015] In a second aspect, the present invention provides an activated carbon-based desulfurizer, which is prepared by the preparation method of the activated carbon-based desulfurizer; the sulfur capacity of the activated carbon-based desulfurizer is 44% to 48%; the removal rate of carbonyl sulfide and carbon disulfide by the activated carbon-based desulfurizer is greater than or equal to 98%, and the removal rate of H2S by the activated carbon-based desulfurizer is greater than or equal to 99%; the removal rate of Cl - The tolerable dose is greater than or equal to 500 mg / m³.

[0016] The application of the technical solution of the present invention has at least the following beneficial effects: On the one hand, the present invention provides a method for preparing an activated carbon-based desulfurizer, and the sulfur capacity of the prepared activated carbon-based desulfurizer can be increased to 44%~48%, and the activation energy of sulfides can be reduced, and the catalysis of organic sulfur (such as COS and CS2) and inorganic sulfur (such as H2S) at 20~50°C can be achieved, which greatly reduces energy consumption; wherein, the removal rates of carbonyl sulfide and carbon disulfide are both greater than or equal to 98%, and the removal rates of H2S are both greater than or equal to 99%. Specifically, the present invention adopts acid washing treatment to remove ash and organic pollutants on the surface of waste activated carbon, release blocked pores, and allow waste activated carbon to be reused; the acid washing treatment can also acid-etch the carbon skeleton of the activated carbon, expand the pore size, and increase the specific surface area of ​​the activated carbon, such as from a specific surface area of ​​800m before the acid washing treatment. 2 / g increased to 1000m3 after pickling 2 / g or more, providing more adsorption sites for the subsequent loading of active components such as cerium salts, iron salts and vanadium salts; furthermore, the acid washing treatment can also enhance the acidification effect of nitric acid through the strong oxidizing effect of hydrogen peroxide, thereby promoting the conversion of functional groups on the surface of activated carbon and the inner wall of the pores into oxygen-containing functional groups (such as -COOH and -OH), thereby obtaining modified activated carbon; these oxygen-containing functional groups can enhance the complexing ability with cerium salts, iron salts and vanadium salts, thereby ensuring that the active components are stably loaded on the surface of the modified activated carbon and the inner wall of the pores. The present invention adopts step S2 and step S3 for stepwise impregnation, which can promote the gradual and uniform loading of cerium salt, iron salt and vanadium salt on the surface of modified activated carbon and the inner wall of the pores to form evenly dispersed active sites, wherein the cerium salt is converted into CeO2 by the second calcination treatment under the air atmosphere in step S5; the iron salt and the vanadium salt are converted into FeVO4 spinel by the second calcination treatment under the air atmosphere in step S5; in step S5, the first calcination treatment is carried out under an inert atmosphere, which can avoid the carbon skeleton of the modified activated carbon from being oxidized and decomposed, thereby While maintaining its porous structure and mechanical strength; the present invention adopts step S4 to form a silane hydrophobic layer on the surface of the modified activated carbon, and there is a microporous structure on the silane hydrophobic layer. Sulfides (such as H2S, COS and CS2) penetrate into the modified activated carbon through the silane hydrophobic layer, and then quickly react with the active sites to generate elemental sulfur; elemental sulfur is bonded to the surface of the modified activated carbon and the inner wall of the pores through van der Waals force or chemical bonds. Due to the increase in the specific surface area of ​​the modified activated carbon treated with acid washing, there are more adsorption sites, which increases the sulfur capacity. Among them, the principle of the reaction to generate elemental sulfur is as follows: Fe in the FeVO4 spinel lattice 3+ and V 5+ It forms a redox pair, reduces the activation energy of the sulfide reaction, and can directly catalyze the oxidation of sulfide to generate elemental sulfur at 20-50°C: 3+ Reduced to Fe by sulfide 2+ , Fe 2+ V 5+ Oxidized to Fe 3+ , and then continue to catalyze the oxidation of sulfide to generate elemental sulfur; V 5+ Fe 2+ Oxidized to Fe 3+ After that, it is restored to V 4+ ; The present invention adopts step S5 of calcination activation to make part of Ce in the CeO2 lattice 4+ Reducing to Ce 3+ , forming oxygen vacancies, which adsorb gaseous O2 to generate reactive oxygen species (such as ·O - ), which can accelerate the oxidation of sulfides into elemental sulfur; in addition, the adsorption of gaseous O2 by oxygen vacancies can convert V 4+ Oxidized to V 5+ , which promotes the Fe in the FeVO4 spinel lattice3+ and V 5+ The cycle of redox pairs can continuously catalyze the oxidation of sulfides to produce elemental sulfur.

[0017] On the other hand, the present invention provides a method for preparing an activated carbon-based desulfurizer, which can improve the chlorine resistance of the prepared activated carbon-based desulfurizer. - The tolerance level was increased to more than 500 mg / m³, which greatly reduced the Cl - Specifically, in step S4, the present invention uses chlorine-resistant hydrophobic treatment to form a silane hydrophobic layer on the surface of the modified activated carbon, Cl - As polar ions, it is difficult for them to penetrate the silane hydrophobic layer and thus they are physically blocked. In addition, negatively charged hydroxylated silane on the silane hydrophobic layer further blocks the Cl - Furthermore, even if there is a microporous structure on the silane hydrophobic layer, the Cl - Will also be Ce 3+ Combined to form CeCl3 precipitate, reducing Cl - Risk of poisoning.

[0018] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 It is the XRD spectrum of the activated carbon-based desulfurizer prepared in Example 1. DETAILED DESCRIPTION

[0020] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0021] Embodiment 1: A method for preparing an activated carbon-based desulfurizer comprises: Step S1, pickling treatment, nitric acid and hydrogen peroxide are mixed at a mass ratio of 4:1 to form a mixed solution; waste activated carbon is mixed with the mixed solution at a mass ratio of 1:4, and then, ultrasonic treatment, rinsing treatment and first drying treatment are performed in sequence to obtain modified activated carbon; the specific surface area of ​​the waste activated carbon before the pickling treatment is 800m 2 / g, increased to 1000m after pickling 2 / g or more; the waste activated carbon is waste activated carbon that adsorbs non-polar or weakly polar pollutants (such as VOCs, H2S, etc.), and avoids the use of waste activated carbon that adsorbs highly polar or heavy metal pollutants (such as chlorine-containing organic matter, Hg 2+ and Pb 2+ Avoid using waste carbon containing a large number of sulfonic acid groups (-SO3H) or strong acidic groups; the ash content of the waste activated carbon is less than or equal to 10%; Step S2, cerium salt loading, immersing the modified activated carbon in a cerium salt solution, and after a first immersion treatment and a second drying treatment, obtaining a cerium salt loaded modified activated carbon; Step S3, iron salt and vanadium salt combined loading, after the iron salt solution and the vanadium salt solution are mixed according to the molar ratio of iron to vanadium of 1:0.4, an organic acid is added, mixed, to obtain a combined salt solution, and the pH value thereof is adjusted to 3.5 with dilute nitric acid; in the combined salt solution, the mass concentration of the organic acid is 1.5%; under the weakly acidic condition of pH 3.5, the carboxylic acid group -COOH of citric acid dissociates into -COO⁻, and reacts with Fe 3+ and V 5+ Form a stable complex to prevent the hydrolysis and precipitation of metal ions (such as Fe(OH)3 or V2O5·nH2O, n represents the amount of crystal water); if the pH value is too high (such as pH>4), Fe 3+ and V 5+ It is easy to hydrolyze to form insoluble precipitates; if the pH value is too low (such as pH < 3), the complexing ability of citric acid decreases, resulting in uneven dispersion of metal ions; The modified activated carbon loaded with the cerium salt is immersed in the combined salt solution, and after a second immersion treatment and a third drying treatment, a modified activated carbon loaded with a combination of iron salt and vanadium salt is obtained; Step S4, chlorine-resistant and hydrophobic treatment, immersing the modified activated carbon treated in step S3 in an alcohol solution containing a silane coupling agent, and sequentially undergoing a third immersion treatment and a fourth drying treatment to obtain chlorine-resistant and hydrophobic modified activated carbon; Step S5, calcination activation, the chlorine-resistant and hydrophobic modified activated carbon is first subjected to a first calcination treatment under an inert atmosphere (specifically nitrogen), and then subjected to a second calcination treatment under an air atmosphere, and finally a calcined activated carbon-based desulfurizer is obtained.

[0022] In the pickling treatment, the mass concentration of the nitric acid is 4%; the mass concentration of the hydrogen peroxide is 1%; The ultrasonic treatment uses an ultrasonic frequency of 40kHz, an ultrasonic power of 300W, and an ultrasonic time of 2h to increase the pickling rate; during the ultrasonic treatment, the temperature of the mixed solution is controlled to be 50°C to further increase the pickling rate; The rinsing treatment uses hot water to rinse the activated carbon after ultrasonic treatment until the pH value of the water flowing out after rinsing is 7; the temperature of the hot water is 80°C; The first drying process uses a drying temperature of 120° C. and a drying time of 4 hours.

[0023] The cerium salt solution is a Ce(NO3)3 solution; the mass concentration of the Ce(NO3)3 solution is 4%; The first soaking treatment adopts a soaking time of 4 hours and a soaking temperature of 23°C; The second drying process uses a drying temperature of 110° C. and a drying time of 2 h.

[0024] The iron salt solution is Fe(NO3)3 solution; the mass concentration of the Fe(NO3)3 solution is 18wt%; The vanadium salt solution is NH4VO3 solution; the mass concentration of the NH4VO3 solution is 6wt%; The second soaking treatment adopts a soaking time of 12 hours and a soaking temperature of 23°C; The second immersion treatment is completed while the combined salt solution is stirred, and the stirring speed is 50 rpm, so that the combined salt solution is fully impregnated and loaded onto the surface of the modified activated carbon and the inner wall of the pores. In addition, the stirring speed should not be too fast to prevent the modified activated carbon from breaking; The third drying process uses a drying temperature of 110° C. and a drying time of 16 hours.

[0025] The organic acid is citric acid.

[0026] The pH value of the combined salt solution is adjusted to 3.5 by using dilute nitric acid; the mass concentration of the dilute nitric acid is 6.5%.

[0027] The mass concentration of the silane coupling agent in the alcohol solution is 2%; the silane coupling agent is KH-550; The third soaking treatment adopts a soaking time of 0.5h and a soaking temperature of 23°C; The fourth drying process uses a drying temperature of 120° C. and a drying time of 4 hours.

[0028] The heating rate used in the first calcination treatment is 5°C / min, until the temperature reaches the target calcination temperature of 250°C, and the holding time is controlled to be 1 hour.

[0029] The heating rate used in the second calcination treatment is 3°C / min, until the temperature reaches the target calcination temperature of 450°C, and the holding time is controlled to be 3h.

[0030] Embodiment 2: Different from Example 1, the mass concentration of the silane coupling agent in the alcohol solution is 2.5%.

[0031] Embodiment 3: Different from Example 1, the mass concentration of the Ce(NO3)3 solution is 3.5%.

[0032] Embodiment 4: Different from Example 1, the mass concentration of the Ce(NO3)3 solution is 4.5%.

[0033] Embodiment 5: Different from Example 1, the mass concentration of the Fe(NO3)3 solution is 22%, and the mass concentration of the NH4VO3 solution is 8%.

[0034] Comparative Example 1: The difference from the first embodiment is that step S2 is cancelled.

[0035] Comparative Example 2: The difference from Example 1 is that the adjustment of the pH value of the combined salt solution in step S3 is cancelled.

[0036] Comparative Example 3: The difference from Example 1 is that the vanadium salt solution in step S3 is eliminated.

[0037] Comparative Example 4: The difference from the first embodiment is that step S4 is cancelled.

[0038] Comparative Example 5: Different from Example 1, the second calcination process in step S5 is eliminated.

[0039] Comparative Example 6: Different from Example 1, the amount of hydrogen peroxide added in step S1 is zero.

[0040] The activated carbon-based desulfurizers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were sampled and Cl -Sulfur capacity test under mass concentration of 500 mg / m³, removal rate test of carbonyl sulfide COS, CS2 and H2S, the test results are shown in Table 1. The test method is as follows: The selected blast furnace gas composition is as follows: H2S mass concentration is 50~200 mg / m 3 (Specifically 200 mg / m 3 )、COS mass concentration is 50~150mg / m 3 (Specifically 150 mg / m 3 ), CS2 mass concentration is 10~50 mg / m 3 (Specifically 50 mg / m 3 ), Cl⁻ mass concentration is 500-650 mg / m³ (specifically 500 mg / m 3 ), at an airspeed of 1000h -1 The test temperature is 30°C and the test is carried out according to ASTM D6646-22 method.

[0041] Table 1 Cl - Test results at a mass concentration of 500 mg / m³

[0042] It can be seen from the data in Table 1 that, compared with Comparative Examples 1 to 6, the sulfur capacity of the activated carbon-based desulfurizer prepared by Examples 1 to 5 of the present invention can be increased to 44% to 48%, and the removal rates of carbonyl sulfide COS and carbon disulfide CS2 are both greater than or equal to 98%.

[0043] By comparing Example 1 and Comparative Example 1, it can be seen that not using step S2 of cerium salt loading will result in a decrease in sulfur capacity. This is because not using cerium salt loading will result in V 4+ Cannot be oxidized to V 5+ , which leads to the Fe in the FeVO4 spinel lattice 3+ and V 5+ The redox pair cannot be recycled, which reduces the generation of sulfur and leads to a decrease in sulfur capacity. On the other hand, it also increases the Cl content of the modified activated carbon. - The risk of poisoning will reduce the catalytic performance of the active components (cerium salts, iron salts and vanadium salts), and the generated sulfur will decrease, resulting in a decrease in sulfur capacity.

[0044] By comparing Example 1 and Comparative Example 2, it can be seen that the pH value is not adjusted, resulting in the pH value of the combined salt solution being too high, which in turn leads to Fe 3+ and V 5+ It is easy to hydrolyze to form insoluble precipitates, which reduces the removal rate of CS2 and COS by the activated carbon-based desulfurizer, and the amount of sulfur generated is small, resulting in a decrease in sulfur capacity.

[0045] By comparing Example 1 with Comparative Example 3, it can be seen that without using the vanadium salt solution, the FeVO4 spinel lattice cannot be formed, that is, there is no Fe 3+ and V 5+ The redox pair causes the removal rate of CS2 and COS by the activated carbon-based desulfurizer to be significantly reduced, and the generated sulfur element is significantly reduced, resulting in a significant decrease in sulfur capacity.

[0046] By comparing Example 1 and Comparative Example 4, it can be seen that the sulfur capacity is reduced when the anti-chlorine hydrophobic treatment is not used. This is because the silane hydrophobic layer cannot be formed on the surface of the modified activated carbon due to the lack of anti-chlorine hydrophobic treatment. - Loss of physical barrier, increase of modified activated carbon Cl - The risk of poisoning will reduce the catalytic performance of the active components, and the generated sulfur will be reduced, resulting in a decrease in sulfur capacity.

[0047] By comparing Example 1 and Comparative Example 5, it can be seen that the removal rate of CS2 and COS by the activated carbon-based desulfurizer is reduced without the second calcination treatment, and the sulfur capacity is reduced. This is because it is difficult to effectively form FeVO4 spinel lattice and CeO2 lattice without the second calcination treatment, resulting in reduced removal rate of CS2 and COS, less generated sulfur, and reduced sulfur capacity.

[0048] By comparing Example 1 and Comparative Example 6, it can be seen that without using hydrogen peroxide, only nitric acid cannot fully oxidize and decompose the organic matter on the inactivated carbon, resulting in that some pores on the activated carbon may be in a blocked state, thereby reducing the sulfur capacity; in addition, without using hydrogen peroxide, only nitric acid is used to promote the conversion of functional groups on the surface of the activated carbon and the inner wall of the pores to generate fewer oxygen-containing functional groups, thereby reducing the complexing ability of cerium salts, iron salts and vanadium salts, resulting in a reduction in sulfur capacity, and the removal rate of CS2 and the removal rate of COS are reduced.

[0049] The activated carbon-based desulfurizer prepared in Example 1 was sampled (i.e., sample 1 to sample 4) and subjected to different Cl - Sulfur capacity test under mass concentration, removal rate test of carbonyl sulfide COS, CS2 and H2S, the test results are shown in Table 2. The test method is the same as above.

[0050] Table 2 Different Cl - Test results under mass concentration conditions

[0051] From the data in Table 2, it can be seen that the activated carbon-based desulfurizer prepared in Example 1 has good chlorine resistance and is - The tolerance level is increased to above 500mg / m³.

[0052] The activated carbon-based desulfurizer prepared in Example 1 was sampled and XRD spectrum tested. The test results are shown in Figure 1 .Depend on Figure 1 It is known that FeVO4 spinel is the core catalytic phase of activated carbon-based desulfurizers. Its high crystallinity (see main peak 35.5°) ensures efficient oxidation of sulfides at low temperatures; CeO2 spinel structure promotes the oxidation of Cl through oxygen vacancies. - The chemical fixation of - Infiltration and CeCl3 chemical fixation) are also possible. Figure 1 The absence of impurity peaks indicates that the preparation process is fully optimized and that the active component can form a stable crystal structure on the carrier, which also indicates that the active component is loaded evenly. On the contrary, if the active component is loaded unevenly, there will be differences in the distribution concentration of the active component, forming non-target crystal phases and generating impurity peaks.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an activated carbon-based desulfurizer, characterized in that: include: Step S1, pickling treatment, mixing nitric acid and hydrogen peroxide in a mass ratio of 3-5:1 to form a mixed solution; mixing the waste activated carbon with the mixed solution in a mass ratio of 1:2-5, and then sequentially subjecting the mixture to ultrasonic treatment, rinsing treatment and first drying treatment to obtain modified activated carbon; Step S2, cerium salt loading, immersing the modified activated carbon in a cerium salt solution, and after a first immersion treatment and a second drying treatment, obtaining a cerium salt loaded modified activated carbon; Step S3, iron salt and vanadium salt combined loading, after the iron salt solution and the vanadium salt solution are mixed according to the molar ratio of iron to vanadium of 1:0.3-0.5, an organic acid is added, mixed, and a combined salt solution is obtained, and the pH value thereof is adjusted to 3-4; in the combined salt solution, the mass concentration of the organic acid is 1%-2%; The modified activated carbon loaded with the cerium salt is immersed in the combined salt solution, and after a second immersion treatment and a third drying treatment, a modified activated carbon loaded with a combination of iron salt and vanadium salt is obtained; Step S4, chlorine-resistant and hydrophobic treatment, immersing the modified activated carbon treated in step S3 in an alcohol solution containing a silane coupling agent, and sequentially undergoing a third immersion treatment and a fourth drying treatment to obtain chlorine-resistant and hydrophobic modified activated carbon; Step S5, calcination activation, the chlorine-resistant and hydrophobic modified activated carbon is first subjected to a first calcination treatment in an inert atmosphere, and then subjected to a second calcination treatment in an air atmosphere, and finally a calcined and activated activated carbon-based desulfurizer is obtained.

2. The method for preparing an activated carbon-based desulfurizer according to claim 1, characterized in that: In the pickling treatment, the mass concentration of the nitric acid is 3.5% to 4.5%; the mass concentration of the hydrogen peroxide is 0.8% to 1.2%; The ultrasonic treatment uses an ultrasonic frequency of 30-50kHz, an ultrasonic power of 300-600W, and an ultrasonic time of 1-2h; during the ultrasonic treatment, the temperature of the mixed solution is controlled to be 40-60°C; The rinsing treatment uses hot water to rinse the activated carbon after ultrasonic treatment until the pH value of the water flowing out after rinsing is 6-7; the temperature of the hot water is 60-80°C; The first drying process uses a drying temperature of 100-120° C. and a drying time of 3-5 hours.

3. The method for preparing an activated carbon-based desulfurizing agent according to claim 1, characterized in that: The cerium salt solution includes a Ce(NO3)3 solution; the mass concentration of the Ce(NO3)3 solution is 3.5% to 4.5%; The first soaking treatment adopts a soaking time of 3-5 hours and a soaking temperature of 20-30°C; The second drying process uses a drying temperature of 100-120° C. and a drying time of 2-4 hours.

4. The method for preparing an activated carbon-based desulfurizer according to claim 1, characterized in that: The iron salt solution includes Fe(NO3)3 solution; the mass concentration of the Fe(NO3)3 solution is 18% to 22%; The vanadium salt solution includes NH4VO3 solution; the mass concentration of the NH4VO3 solution is 6% to 8%; The second soaking treatment adopts a soaking time of 10-14 hours and a soaking temperature of 20-30°C; The second immersion treatment is completed while the combined salt solution is stirred at a stirring speed of 50 rpm; The third drying process uses a drying temperature of 100-120° C. and a drying time of 15-20 hours.

5. The method for preparing an activated carbon-based desulfurizer according to claim 1, characterized in that: The waste activated carbon is waste activated carbon that adsorbs non-polar or weakly polar pollutants; the specific surface area of ​​the waste activated carbon is greater than or equal to 800 m 2 / g, ash content is less than or equal to 10%; The organic acid includes citric acid.

6. The method for preparing an activated carbon-based desulfurizing agent according to claim 1, characterized in that: The pH value of the combined salt solution is adjusted to 3-4 by using dilute nitric acid; the mass concentration of the dilute nitric acid is 5%-8%.

7. The method for preparing an activated carbon-based desulfurizing agent according to claim 1, characterized in that: The mass concentration of the silane coupling agent in the alcohol solution is 2% to 2.5%; the silane coupling agent includes KH-550; The third soaking treatment adopts a soaking time of 0.5-2 hours and a soaking temperature of 20-30°C; The fourth drying process adopts a drying temperature of 100-120° C. and a drying time of 3-5 hours.

8. The method for preparing an activated carbon-based desulfurizing agent according to claim 1, characterized in that: The heating rate used in the first calcination treatment is 2-5°C / min, until the temperature reaches the target calcination temperature of 200-300°C, and the holding time is controlled to be 1-3h.

9. The method for preparing an activated carbon-based desulfurizing agent according to claim 1, characterized in that: The heating rate used in the second calcination treatment is 2-5°C / min, until the temperature reaches the target calcination temperature of 300-500°C, and the holding time is controlled to be 2-4h.

10. An activated carbon-based desulfurizer, characterized in that: The method for preparing the activated carbon-based desulfurizer as claimed in claims 1 to 9 is adopted; the sulfur capacity of the activated carbon-based desulfurizer is 44% to 48%; the removal rate of carbonyl sulfide and carbon disulfide by the activated carbon-based desulfurizer is greater than or equal to 98%, and the removal rate of H2S by the activated carbon-based desulfurizer is greater than or equal to 99%; the removal rate of Cl - The tolerable dose is greater than or equal to 500 mg / m³.

Citation Information

Patent Citations

  • Low-temperature denitration and synergetic desulfurization active carbon catalyst and preparation method thereof

    CN104190432A

  • Blast furnace gas desulfurization catalyst as well as preparation method and application thereof

    CN112058273A

  • Method for desulfurizing a gas and absorbent suitable for this method

    WO1994014525A1